Interfacial polarization-induced high-k polymer dielectric film for high-performance triboelectric devices. (April 2021) - Kim, Minsoo P.; Ahn, Chang Won; Lee, Youngsu; Kim, Kyoungho; Park, Jonghwa; Ko, Hyunhyub
Abstract: Output performance of triboelectric devices critically depends on their surface charge density that is greatly influenced by the dielectric constant of material. However, contrary to polymer composites, the dielectric constant cannot be substantially increased in pure polymers. This study shows that interfacial polarization in bilayer polymer films significantly enhances their dielectric constants, increasing the surface charge density and triboelectric performance. This is the first report of the introduction of interfacial polarization of dielectric materials for the enhancement of triboelectric output performance. The elastic bilayer films consisting of polydimethylsiloxane (PDMS) coated with poly (2, 2, 2-trifluoroethyl methacrylate) (PTF) and poly (L -lysine) (PLL) as negative and positive triboelectric materials, respectively, are utilized in triboelectric devices, which show a dramatic increase in the dielectric constants (24.4 for PTF-PDMS and 15.2 for PLL-PDMS bilayers at 10 kHz) through interfacial polarization, resulting in significant enhancement of triboelectric performance when compared with hard single-layer films. For proofs of concept, we fabricated a temperature-sensitive triboelectric sensor and vibration-based triboelectric nanogenerator. The sensor showed the highest temperature sensitivities among triboelectric sensors whereas the nanogenerator provided vibration-induced sustainable power for LED operation without rectification, which was attributed to the charge accumulation in the bi-layered dielectric films. Graphical Abstract: We demonstrate that the elastic bilayer films in triboelectric devices exhibit a dramatic increase in the dielectric constants through interfacial polarization, resulting in greatly enhanced surface charge density and triboelectric output performances. As proofs of concept, we develop novel triboelectric applications such as a temperature-sensitive triboelectric sensor with an ultrahigh sensitivity and a vibration-based triboelectric nanogenerator with sustainable power even without rectification. ga1 Highlights: Elastic bilayer film shows significant enhancement of triboelectric performance through effective interfacial polarization. Temperature-responsive triboelectric sensor with the best temperature sensitivity is achieved. Vibration-induced triboelectric nanogenerator with DC behavior is developed.